2013
DOI: 10.1016/j.pmrj.2013.08.604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Weight–Supported Treadmill Gait Training on Balance in Patients With Parkinson Disease

Abstract: PWSTT may be a better interventional choice than CGT for gait and balance rehabilitation in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 32 publications
5
56
1
7
Order By: Relevance
“…All subjects with PD were "on" PD medication during data collection. The eligibility criteria for all subjects were: age between 60 and 80 years, no pain, fracture or severe soft tissue injury in the past 6 months, no cardiovascular, respiratory or cognitive impairments (score >24 in the Mini Mental State Examination) [15]. Equipment -The Bluetooth Channels Myotrace 400 (Noraxon®) biological sampling module, with a sampling frequency of 2000 Hz, a 500-fold gain amplifier, and a 16-bit analogue / digital conversion card with 4 channels was used to collect the EMG data with bipolar Ag / AgCl surface electrodes 1cm in diameter and with an inter-electrode distance of 2cm.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects with PD were "on" PD medication during data collection. The eligibility criteria for all subjects were: age between 60 and 80 years, no pain, fracture or severe soft tissue injury in the past 6 months, no cardiovascular, respiratory or cognitive impairments (score >24 in the Mini Mental State Examination) [15]. Equipment -The Bluetooth Channels Myotrace 400 (Noraxon®) biological sampling module, with a sampling frequency of 2000 Hz, a 500-fold gain amplifier, and a 16-bit analogue / digital conversion card with 4 channels was used to collect the EMG data with bipolar Ag / AgCl surface electrodes 1cm in diameter and with an inter-electrode distance of 2cm.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was calculated based on a study by Ganesan et al (13) . Functional balance measured using the Berg scale was considered for the calculation due to the fact that this scale represents an important clinical outcome and is directly related to the proposed intervention.…”
Section: Sample Sizementioning
confidence: 99%
“…3,15,28,30,37,40,47,56,63 There are also a number of recent studies that have examined the efficacy of specific therapy techniques, including some novel approaches. 36,37,55,62,[64][65][66][67] These are summarized in Table 2.…”
Section: Therapy Techniquesmentioning
confidence: 99%
“…Improvements in a range of outcomes have been shown with advanced balance exercises, 37 dance, 55 tai chi, 36 resistance training 65,66 and aerobic exercise, such as treadmill training 67 ( Table 2). A recent systematic review of musicbased movement therapy has also found small, but significant benefits in balance, functional mobility and gait.…”
Section: Therapy Techniquesmentioning
confidence: 99%